Image Based Smartphone Application for Purisha Pariksha – An Exemplar for Digital Health - Harijan, Ravikumar Hanamanth; Yadav, Chhaju Ram; Singh, Bhanu Pratap (International Research Journal of Ayurveda & Yoga, 2024)
A wide, multidisciplinary notion called “digital health” or “digital healthcare” is an intersection between technology and healthcare. The purpose of the Global strategy on digital health (2020-2025) is to strengthen health systems through the application of digital health technologies for consumers, health professionals, health care providers and industry towards empowering patients and achieving the vision of health for all. Stool examination is one among the prime laboratory investigative tool in Medicine and in so many conditions it helps to confirm the diagnosis. Dosha, Dhatu, Agni and Mala are main factors to define Swastha and Aswastha awastha of an individual. And in Astha Sthana Pariksha, Mala Pariksha stands on third place. Purisha Pariksha have been mentioned in various disease conditions by Brihatrayi in scattered manner. This work should be done with collaboration of Advance technical experts. Images of different conditions of Purisha Pariksha are collected with special reference to Classical text books. In back-end, Machine learning algorithms using Python language to process the image of Purisha. In front end, we can use app for user interface. This attempt may help to differentiate physiological and pathological Purisha, by the Image based smartphone app.This innovative project may help to assess Agnibala, Symptoms of abnormal dosha, Ama and Niraama Mala for the well-being of entire mankind. We have already touch down twenty-first century, an era of digitalization and modernization. So, evidence based studies are only valid today, it is inevitable to incorporate technology for more acceptability and understanding of various Ayurvedic concepts at global level.